Septic Shock Management Using Continuous Renal Replacement Therapy in a Postpartum Patient with Diabetic Ketoacidosis, Acute Kidney Injury, and Ventilator-Associated Pneumonia - Putra, Prana Indra; Pradian, Erwin (Journal of Society Medicine, 2025)
Introduction: Postpartum sepsis in patients with pregestational diabetes mellitus is a life-threatening condition that may precipitate acute kidney injury (AKI) and diabetic ketoacidosis (DKA). Sepsis frequently leads to multiorgan dysfunction, with the kidneys being particularly vulnerable. Severe AKI in septic shock often requires renal replacement therapy. Continuous Renal Replacement Therapy (CRRT), particularly in hemodynamically unstable patients, is the preferred modality due to its gradual solute and fluid removal, cytokine modulation, and ability to manage complex acid-base disturbances. In this setting, secondary ventilator-associated pneumonia (VAP) further complicates management. Case Description: A 35-year-old woman with pregestational type 2 diabetes mellitus developed septic shock with DKA following spontaneous vaginal delivery. She presented with refractory hypotension, severe metabolic acidosis (pH 6.98), hyperglycemia (301 mg/dL), ketonuria (2+), and oliguria (0.3 mL/kg/h). Serum creatinine rose from 0.85 to 3.61 mg/dL, fulfilling KDIGO stage 3 AKI criteria. During ICU stay, the patient developed VAP, necessitating prolonged mechanical ventilation and targeted antimicrobial therapy. Conclusion: Early initiation of Continuous Veno-Venous Hemodiafiltration (CVVHDF) using bicarbonate-buffered replacement fluid and an oXiris filter effectively corrected severe acidosis (pH 7.255 → 7.359 within 76 hours), removed ketones and inflammatory mediators, stabilized hemodynamics, and facilitated renal recovery while reducing vasopressor requirements. Multidisciplinary management, including strict VAP prevention bundle and culture-directed antibiotics, enabled successful extubation. Timely high-volume CRRT combined with comprehensive critical care is crucial in managing complex postpartum septic shock with DKA and AKI.